Considering the relationship between quantitative parameters and prognostic factors in breast cancer: Can mean standardized uptake value be an alternative to maximum standardized uptake value? - Reyhan Köroglu; İsmail Köksal; Fikri Şimşek; Fatma Gezer; Ersoy Kekilli; Bülent Ünal (World Journal of Nuclear Medicine)
It was aimed to investigate the correlation between maximum standardized uptake value (SUVmax), mean standardized uptake value (SUVmean), and retention index (RI), which represents the quantitative evaluation of the uptake of 18F-fluoro-2-deoxy-D-glucose (18F-FDG) used in positron emission tomography (PET) and clinicopathologic as well as biologic prognostic factors. Forty-one women with breast cancer who were histopathologically diagnosed were included in this study. Neoadjuvant chemotherapy was applied to all patients before PET/computed tomography (CT). After FDG injection, PET/CT screening was applied within the 1st h (PET-1) and in the 2nd h (PET-2). SUVmax, SUVmean, SUVmax RI, and SUVmean RI of every image were calculated qualitatively and semiquantitatively. The correlation between quantitative and semiquantitative PET parameters and biologic as well as clinicopathologic prognosis factors was evaluated. Statistically, significant positive correlation was found between lymph nodes (LNs), which were evaluated by clinical picture, clinical stage as well as histopathologically and quantitative PET parameters (SUVmax1, SUVmax2, , RImax, SUVmean1, SUVmean2, RImean) (P < 0.05). While statistically significant correlation with RImax was detected only by LN (histopathological), correlations with RImean were detected by clinical picture, clinical stage, metabolic stage, and LN (histopathological). Statistically, significant correlation was found between RImax and estrogen receptor in patients who were histopathologically diagnosed with invasive ductal carcinoma (n = 34) (P < 0.05). We detected correlations between biologic and clinicopathologic prognostic factors and SUVmax as well as SUVmean values in breast carcinoma. SUVmean values may provide important knowledge when the correlation between prognostic factors and PET parameters is investigated even if they are not used routinely.